ESTIMATION OF THE ANTIOXIDANT ACTIVITY OF LOCAL CAPPARIS SPANOSA LEAVES - & Al Janabi, Al Badri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The objective of this experiment was to estimate the antioxidant actitivity of the plant Capparis spinosa leaves were collected during (April- Sept,2017) from Baghdad. Water and alcohol extracts were prepared from them and more methods were used to estimate the antioxidant efficacy, the iron binding method, The hydrolysis of hydroxide peroxide and the effect of free radical inhibiting. The water extract of alkaline leaves for April and May samples was characterized by the correlation of iron ion (97.8 and 98.1%) respectively, as well as the alcoholic extract of the April,June,July (89.47, 95.5 and 96.9%) respectively at same concentration of 10 mg / ml, these samples were superior to EDTA-Na and citric acid with 94.73% and 81% respectively at same concentration. The water and alcohol extracts of April and May samples were superior to the water and alcohol extracts of the other samples , and the highest percentage of hydrogen Peroxide inhibitor in the water extracts of the months (April, June, July and September) of 4.3%, 4.2%, 4.3% and 4% respectively, and the alcohol extract for May, June, July and August (4.3, 4.2, 4.3 and 4.2% )respectively at same concentration 400 μg / mL, These percentages are higher than that of industrial oxidants than BHT (3.9%) in the same concentration. The water extract for August and Abstract samples (87%) and 85.74% respectively (1250 μg / ml) on the water and alcohol extracts of the rest of the samples in the manner of effective suppression of free radicals. However, these percentages were lower than the percentage of ascorbic acid of 87.56% for the same concentration.